Inclusion in Higher Education - Sanchez, Cintia Nazaré Madeira; Pasian , Mara Silvia (Seven Editora, 2023)
Currently, one cannot discuss education without considering the inclusion of people with disabilities. In Brazil and in the world this movement had as a landmark the Declaration of Salamanca in 1994 which has as its main principal education for all, enabling access to regular education. The opportunity to be in regular education enabled the student to have access to higher education that has a new demand to think strategies to ensure accessibility and inclusion. The objective of the research was to analyze the educational, attitudinal, and communicational strategies of inclusion that are being carried out in higher education by professionals who work in specialized educational care so that the student has opportunities for learning equity. Method: qualitative research, in which nine professionals who work in specialized educational care in higher education were interviewed. Results and discussion: the data showed that higher education institutions make adaptations according to the legislation. Final considerations: Higher education has made adaptations to ensure inclusion and equity to create an inclusive culture. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-151